Structural, electrochemical, and adsorption studies of Ni and Zn benzylimidazole coordination polymers with terephthalate linkers - Sherino, Bibi; Mohamad, Sharifah; Manan, Ninie Suhana Abdul; Tareen, Huma; Yamin, Bohari Mohd; Halim, Siti Nadiah Abdul (Springer Verlag, 2018)
Two coordination polymers, [Ni(bim)2(L1)(H2O)2]n (CP-1) and [Zn(bim)(L1)(Cl)]n (CP-2) (bim = 1-benzylimidazole, L1 = terephthalic acid), were synthesized and characterized by physicochemical and spectroscopic methods. The Ni(II) center in CP-1 is octahedral, while the Zn(II) center in CP-2 is tetrahedral. CP-1 and CP-2 were used to modify carbon paste electrodes to assess their effect on the electrochemical behavior of ferricyanide. The redox reactions of ferricyanide on both electrodes proved to be reversible and diffusion controlled, with ferricyanide diffusion coefficients for CP-1 and CP-2 of 1.88 × 105 and 3.44 × 105 cm2 s−1, respectively. These coordination polymers were also investigated for their adsorption behavior toward two dyes: Chicago sky blue and methylene blue. CP-1 and CP-2 both rapidly adsorbed the anionic Chicago sky blue dye by different intermolecular interactions; in contrast, the cationic methylene blue dye was adsorbed to a lesser extent. The adsorption of these CPs depends on the charge but not the size of the dye. Addition of methanolic potassium nitrate solution caused the release of the adsorbed dyes.